Flow field characterization in a vertically oriented cold wall CCVD reactor by particle image velocimetry - Reinhold Lopez, Karla; Bräuer, Andreas; Schmitt, Adeliene; Popovska, Nadejda; Leipertz, Alfred (Chemical Engineering Journal, 2012)

Functionalization of polymer powders for SLS-processes using an atmospheric plasma jet in a fluidized bed reactor - Sachs, Marius; Schmitt, Adeliene; Schmidt, Jochen; Peukert, Wolfgang; Wirth, Karl-Ernst (AIP Conference Proceedings 1664, 2015)
Recently additive manufacturing processes such as selective laser sintering (SLS) of polymers have gained more importance for industrial applications [1]. Tailor-made modification of polymers is essential in order to make these processesmore efficient and to cover the industrial demands. The so far used polymer materials show weak performance regarding the mechanical stability of processed parts. To overcome this limitation, a new route to functionalize the surface of commerciallyavailable polymer particles (PA12; PE-HD; PP) using an atmospheric plasma jet in combination with a fluidized bed reactor has been investigated. Consequently, an improvement of adhesion and wettability [2] of the polymer surface without restraining the bulk properties of the powder is achieved. The atmospheric plasma jet process can provide reactive species at moderate temperatures which are suitable for polymer material. The functionalization of the polymer powders improves the quality of the devices build in a SLS-proces
Keywords: Atmospheric Plasma Jet; Polymer Functionalization; Fluidized Bed Reactor; SLS-Process

Functionalization of polymers using an atmospheric plasma jet in a fluidized bed reactor and its impact on selective laser melting processes - Sachs, Marius; Schmitt, Adeliene; Schmidt, Jochen; Peukert, Wolfgang; Wirth, Karl-Ernst (11th International Conference on Fluidized Bed Technology, CFB 2014, 2014)
In order to improve thermoplastic particles (e.g. Polyamide, Polypropylene and Polyethylene) for Selective Laser Melting (SLM) processes a new approach for functionalization of temperature-sensitive polymer powders at large scales is investigated. This is achieved by combining an atmospheric pressure plasma jet and a fluidized bed reactor. Using pressurized air as plasma gas, radicals including OH* are generated. The functionalization leads to an increase of surface energy of the treated polymer powder without changing the bulk properties. Application of the functionalized polymers in a SLM process to build single layers leads to an improvement of the melted layer
Keywords: Atmospheric pressure plasma jet; Polymer functionalization; Fluidized bed reactor

Functionalization of polymers using an atmospheric plasma jet in a fluidized bed reactor and the impact on SLM-Processes - Sachs, Marius; Schmitt, Adeliene; Schmidt, Jochen; Peukert, Wolfgang; Wirth, Karl-Ernst (29th International Conference of the Polymer Processing Society, 2014)
In order to improve thermoplastics (e. g. Polyamide, Polypropylene and Polyethylene) for Selective Laser Beam Melting (SLM) processes a new approach to functionalize temperature sensitive polymer powders in a large scale is investigated. This is achieved by combining an atmospheric pressure plasma jet and a fluidized bed reactor. Using pressurized air as the plasma gas, radicals like OH* are created. The functionalization leads to an increase of the hydrophilicity of the treated polymer powder without changing the bulk properties. Using the polymers in a SLM process to build single layers of melted material leads to an improvement of the melted layers.
Keywords: fluidized bed reactor; atmospheric pressure plasma jet; polymer functionalization